Recovery of Nonlinear Heart Rate Variability After Submaximal Exercise in Young Persons With Symptoms of Anxiety and Depression - Benjamim, Cicero Jonas R.; Moraes Pontes, Yasmim M. de; Mangueira, Luana B.; Pascoaloti-Lima, Julio Cesar; Rodrigues, Guilherme da Silva; Bueno, Carlos Roberto; Garner, David M.; Valenti, Vitor E. [UNESP] (Soc Chaos Theory Psychology & Life Sciences, 2022)
Prior studies have demonstrated that anxiety and depression explain the increase of adverse cardiovascular events and failure to modulate cardiac activity. This study of the nonlinear heart rate (HR) variability (HRV) behavior can provide additional information concerning the autonomic recovery of HR after exercise. The dynamics of these indices in exercise-mediated situations may reveal other ways to assess HRV recovery after physical effort. We studied nonlinear HRV recovery after submaximal exercise in subjects with higher Hospital Anxiety and Depression Scale (HADS) scores. Sixty-six young adults were recruited, and 50 completed the HADS rating scale to quantify their degree of anxiety and depression for later allocation to a suitable group. After experimental procedures, the final sample involved 20 participants (15 female) who were allocated to the group with low HADS scores (LHADS) and 21 (16 female) to the group with high HADS scores (HHADS). We logged HRV data before and during recovery from submaximal aerobic exercise and analyzed this data using symbolic analysis. Young adults with High HADS scores (HHADS) had a slower recovery of the symbolic analysis of HRV via index 2LV% (two like variations) and 2ULV% (two unlike variations) after aerobic exercise. Participants with higher HADS scores presented delayed nonlinear HRV recovery after submaximal exercise.
Keywords: anxiety; depression; heart rate variability; cardiovascular physiology; exercise